The onset of coastal foredune formation at variable levels of ecological complexity - Charbonneau, Bianca R.; Zinnert, Julie C.; Wnek, John; Williams, Amy; McGivney, Eric; Matthews, Kailey; Sabo, Alexander; Dohner, Stephanie M. (Frontiers in Ecology and Evolution, 2026)
Gaps in our understanding of the interplay between biotic and abiotic forces shaping coastal dunes inhibit our ability to fully understand their evolution and predict topographic changes. The theoretical evolution of a dune system begins with nebkha formation. This formation begins around individual dune-building plants, which grow over time around groups of plants. Individual nebkha mounds can meld into one another, growing in size and complexity based on the dune-building vegetation population. To better understand ecogeomorphological feedbacks driving these relationships, we tested how plant density impacts nebkha formation by Ammophila breviligulata in both a laboratory and a field setting. Laboratory tests consisted of using a wind tunnel to control abiotic forces, focusing on the effects of varying plant density in nebkha formation. We tested three low densities commonly supporting backshore nebkha: an individual (one plant) and small groups (five and nine plants). In the field, we used both remote sensing and field techniques to quantify the relationship between stem density and the nebkha shape and size of backshore A. breviligulata nebkha. In the wind tunnel, stem density was not as strong a predictor of nebkha size or shape as number of leaves and aboveground biomass, both of which increased with growing stem and plant densities. Stem density was a strong predictor of nebkha size and shape, with increasing variability at increasing densities in both the laboratory and field. In situ measurements of stem density are performed inconsistently among field experiments due to the effort required. Therefore, strong allometric scaling among A. breviligulata morphology metrics can help overcome limitations around what can be collected in the field or in a modeled environment containing limited plant metrics. In situ, vegetation stabilization frequently allowed the nebkha to grow steeper than would be expected based on grain size and the angle of repose. These differences in field and laboratory nebkha highlight the importance of grounding laboratory work in field collections for the interpretation of their results in nature. Understanding the underlying ecogeomorphic feedbacks involved in nebkha formation is critical to scaling up modeling efforts to forecast coastal foredune evolution, recovery, and storm response in the face of climate change.